ドライバレー チイキ ノ エンコ ノ セイセイ カテイ ニ ツイテ - 中谷, 周; ナカヤ, シュウ; 西村, 雅吉; ニシムラ, マサキチ; NAKAYA, Shyu; NISHIMURA, Masakichi (国立極地研究所, 1977)
P(論文) ドライバレー地域に点在する3つの塩湖,バンダ,ボニー,フリクセルの各湖について,底層にみられる高塩分濃度水の生成過程および塩成層生成年代について考察した.高塩分濃度水は,海水組成を有するうすい水,あるいぱ海塩を起源水として,長年月の蒸発,濃縮により現在の底層水濃度まで濃縮された.その過程において,岩石,堆積物等とのイオン交換反応がおこり,Na^+,K^+は溶液から失われ,Ca^<2+>,Mg^<2+>は溶液へ与えられ,Ca^<2+>の一部はCaSO_4として沈積したことで説明できる.底層水の濃度傾斜については,形成期の塩湖はきわめて小さな氷河湖であった.その氷河湖へ大きな気候変動があり,周辺氷河融水が流入し,底層の高塩濃度水中の化学成分は底層から上層へ分子拡散,またはイオン拡散により拡散し,現在のような鉛直分布となった.この考えに基づいて,Fickの式,塩の拡散係数,実測塩濃度を用いて計算,その結果,1,000～1,250年前に気候変動があったと考えられる. A simple model is proposed for the present chemical composition of the saline lakes in the Dry Valleys. A diluted water of sea salt whose compositional ratio was that of sea water was concentrated by evaporation to the present chlorinity. During the concentration process, a part of Na^+ and K^+ replaced Ca^<2+> and Mg^<2+> of the sediment or weathering rock, and some part of CaSO_4 deposited from the solution. All the reaction proceeded under an ionic massbalance. This simple idea can beautifully explain the origin of the chemical compositions of Lakes Vanda and Bonney. The salt concentration profiles in these saline lakes can be explained by the molecular diffusion (or ionic diffusion) of dissolved chemical substances from the bottom layer to the surface layer. The vertical transport of salt from the bottom layer is given by a conventional Fickian equation, with a diffusion coefficient (D); [numerical formula] where C is the salt concentration, z is the vertical distance coordinate increasing upward from z=0 at the bottom to z=h at the top of the saline layer, and t is time. For eq. (1), the initial and boundary conditions are [numerical formula] [numerical formula] [numerical formula] The solution of (1), obtained by the Laplace transformation with the boundary conditions (2)-(4) is [numerical formula] whereφ_1 is a function of time (t), height (z), and diffusion coefficient (D), its complete form being [numerical formula] The value of t of these saline lakes in the Dry Valleys is estimated by trial and error computation using eq. (5) and ...